2021
DOI: 10.15252/embr.202152948
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IRGM establishes a robust antiviral immune state to restrict pathogenic viruses

Abstract: The type I interferon (IFN) response is the major host arsenal against invading viruses. IRGM is a negative regulator of IFN responses under basal conditions. However, the role of human IRGM during viral infection has remained unclear. In this study, we show that IRGM expression is increased upon viral infection. IFN responses induced by viral PAMPs are negatively regulated by IRGM. Conversely, IRGM depletion results in a robust induction of key viral restriction factors including IFITMs, APOBECs, SAMHD1, teth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…TANK-binding kinase 1 ( TBK1 ) is a Ser/Thr kinase with a central role in coordinating the cellular response to invading pathogens and regulating key inflammatory signaling cascades. Some genes play an important role in the antiviral mechanism of cells, such as TBK1 , IRGM and so on ( 60 , 61 ). Studies have shown that TBK1 is also associated with cancers, such as kidney cancer, cervical cancer, and lung cancer ( 62 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…TANK-binding kinase 1 ( TBK1 ) is a Ser/Thr kinase with a central role in coordinating the cellular response to invading pathogens and regulating key inflammatory signaling cascades. Some genes play an important role in the antiviral mechanism of cells, such as TBK1 , IRGM and so on ( 60 , 61 ). Studies have shown that TBK1 is also associated with cancers, such as kidney cancer, cervical cancer, and lung cancer ( 62 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, all mice were monitored every day up to 8 dpi. According to the symptom-based disease outcomes (no symptoms, 0; fur rise, 1; hunchback, 2; one hind limb paralysis, 3; both hind limb paralysis, 4; and death, 5), the clinical scores of each mice were tabulated on daily basis for the survival curve analysis ( 56 , 58 , 61 ).…”
Section: Methodsmentioning
confidence: 99%
“…IRGM is also a fundamental negative regulator of type-1 IFN response against viral pathogens [21,55]. IRGM plays a key role in replication of HCV, an important risk factor for hepatocellular carcinoma, by regulating Golgi fragmentation and leading to co-localization of Golgi vesicles with replicating HCV [48].…”
Section: Irgm During Microbial Insultmentioning
confidence: 99%
“…This may aid in viral survival by autophagic degradation of nucleic acid-sensing proteins RIG-I and cGAS [21]. Epithelial and monocytic cells lines with abolished IRGM demonstrate enhanced antiviral properties, including MHC-I presentation and PKR stress granule formation, and are resistant to ZIKV and SARS-CoV-2 infection [55].…”
Section: Irgm During Microbial Insultmentioning
confidence: 99%